Equilibrium Moisture Content Modeling and Study of Circulating-Bed Drying Kinetics of Non-Fragrant and Fragrant Paddy Varieties - Taveesuvun, Chitsanu; Tirawanichakul, Supawan; Tirawanichakul, Yutthana (Trends in Sciences, 2022)
Due to maintaining good quality of rice grain kernel varieties during post-harvesting and in-store period, the thermos-physical properties which relate to surrounding conditions (temperature and relative humidity) of each rice variety are essential, especially on its moisture content and diffusion mechanism. Therefore, the main objectives of this research are to determination of the thermo-physical properties (in terms of equilibrium moisture content (EMC) and effective diffusivity (Deff)) of local non-glutinous GorKhor55 (RD55) and Hom Thammasat (HT) paddy varieties and to field experiment study of the small-scale circulating-bed dryer with capacity of 1 - 1.5 ton. The EMC experiment using gravitational method is carried on and the experimental results are simulated by non-linear regression analysis. The results show that the predicted data using Modified Oswin model is the most suitable fitting to the exact EMC data for both paddy varieties. The effective diffusivity of both paddy varieties is the function of inlet drying temperature. For the last purpose of this work, the drying kinetics of RD55 and HT paddy varieties with initial moisture content (MC) of 20.1 and 24.6 % dry-basis, respectively are studied using the circulating-bed technique. The inlet drying temperature is set as 45 and 55 °C including operation conditions of 1 stage and 2 stages circulating-bed drying. The inlet air velocity is fixed at 0.41 m/s and the grain mass flow rate of circulation is 0.23 kg/s. The desired final MC after drying of each experiment is in ranges of 16.5 - 16.8 % dry-basis. All of experimental data are non-linear regression analyzed by conventional drying equation models and the simulation results stated that the most suitable model for the circulating-bed drying of RD55 variety with inlet drying temperature of 45 and 55 °C is the Logarithmic and Approximation of diffusion model, respectively. HIGHLIGHTS The special parameter of equilibrium moisture content value of these two rice varieties have been firstly determined The compact circulating-bed dryer with LPG fuel source for farmer community has been tested and run. The drying kinetics models for both rice varieties were evaluated among drying temperature of 45 - 50 deg. Celsius From the Fick’s law of diffusion, the effective diffusion coefficient of the rice varieties were determined and formulated the relationship between this coefficient and drying temperature